Travel guide Japan (Japan Travel Bureau, 1977)
Here is a handy guidebook to carry with you on your travels throughout Hapan. In addition to giving useful information about the main cities and resorts, it tells you where to stay, what kind of food you can enjoy, where to buy good souvenirs and even what hobbies to take up.